Green Synthesis of Zinc Oxide Nanoparticles by Justicia adhatoda Leaves and Their Antimicrobial Activity - Pachaiappan, Rekha; Rajendran, Saravanan; Ramalingam, Gomathi; Vo, Dai-Viet N.; Priya, P. Mohana; Soto-Moscoso, Matias (Chemical engineering & technology, 2021)
Zinc oxide is recognized as one of the best antimicrobial agents. Zinc oxide nanoparticles were fabricated through a green approach using zinc sulfate, zinc nitrate, and zinc acetate dihydrate as precursors and an extract of Justicia adhatoda leaves as a reducing agent. The synthesized zinc oxide nanoparticles were checked for their antimicrobial activity against the bacterial strains Staphylococcus aureus, Escherichia coli, Pseudomonas aeruginosa, and the fungal strains Aspergillus niger, Aspergillus flavus, and Aspergillus fumigates. All three zinc oxide nanoparticles were found to inhibit the growth of microbes by the release of zinc ions and production of reactive oxygen species followed by destruction of microbes. Antimicrobial results of zinc oxide nanoparticles from the three different precursors were compared. Green synthesis of zinc oxide nanoparticles was performed with zinc sulfate, zinc nitrate, and zinc acetate dihydrate as precursors by employing Justicia adhatoda leaf extract as a reducing and capping agent. All three zinc oxide nanoparticles successfully inhibited the growth of microbes by releasing zinc ions and production of reactive oxygen species followed by destruction of the microbes.